PEMIKIRAN KH. MUHADJIRIN AMSAR AL-DARY (1924-2003) DALAM KITAB MISHB?H AL-DHAL?M: SYARH BUL?GH AL-MAR?M MIN ADILLAH AL-AHK?M - Nur, Mahmudah (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2018)
This paper examines the thoughts of KH. Muhadjirin Amsar Al-Dary in Mishb?h al-Dhal?m: Syarh Bul?gh al-Mar?m min Adillah al-Ahk?m. The book is one of the results of a phenomenal writing, when he studied in Makkah and Medina. This study uses the approach of Philology and Phenomenology, which are used as the analytical tool to obtain information from a text through the work of KH. Muhadjirin Amsar Ad-Dary (1924-2003) and to reveal facts in a certain time span based on the views of a group of people or someone who is considered representative. This study shows that the main characteristics and identity of KH. Muhadjirin’s work viewed from the systematic of Mishb?h al-Dhal?m: Syarh Bul?gh al-Mar?m min Adillah al-Ahk?m, very clearly visible. In the book, he presents several studies which describe the differences among several schools, especially the popular school of jurisprudence. Keywords: syarh, kitab, KH. Muhadjirin.